Screening of advanced breeding lines for high temperature tolerance using biochemical parameters in Indian mustard (Brassica juncea) - MAWLONG, IBANDALIN; SINGH, V V; RAM, BHAGIRATH; GARG, PANKAJ; RANI, REEMA; KUMAR, M S SUJITH; GURUNG, BISHAL; RAI, P K (The Indian Journal of Agricultural Sciences, 2020)
A set of 30 advanced breeding lines of Brassica juncea were screened for heat tolerance in terms of biochemical parameters in field condition at ICAR-DRMR. The selection was based on (1) early sowing (ES) (September) when average soil temperature was 41ᵒC and atmospheric temperature was around 35ºC so that heat stress coincided with seedling growth and (2) normal sown (NS) (mid October) where soil temperature was 34.2ᵒC so that seedling growth did not coincide with any stress. Various biochemical parameters like total chlorophyll, total carotenoid content, total antioxidant capacity, radical scavenging activity, lipid peroxidation and proline content were measured in leaves at flowering stage to evaluate the variability among the genotypes and comparison between ES and NS was done. Stress susceptibility index (SSI) categorized genotype NPJ-124 and DRMR-1165-40 to be highly tolerant. Correlation analysis among all the traits showed total antioxidant capacity to be significantly correlated to carotenoids and chlorophyll pigment levels showing the importance of these parameters as indices for screening.